STE20‐Type Protein Kinase MST4 Controls NAFLD Progression by Regulating Lipid Droplet Dynamics and Metabolic Stress in Hepatocytes. Issue 7 (16th March 2021) - Caputo, Mara; Cansby, Emmelie; Kumari, Sima; Kurhe, Yeshwant; Nair, Syam; Ståhlman, Marcus; Kulkarni, Nagaraj M.; Borén, Jan; Marschall, Hanns‐Ulrich; Blüher, Matthias; Mahlapuu, Margit
Abstract : Nonalcoholic fatty liver disease (NAFLD) has emerged as a leading cause of chronic liver disease worldwide, primarily because of the massive global increase in obesity. Despite intense research efforts in this field, the factors that govern the initiation and subsequent progression of NAFLD are poorly understood, which hampers the development of diagnostic tools and effective therapies in this area of high unmet medical need. Here we describe a regulator in molecular pathogenesis of NAFLD: STE20‐type protein kinase MST4. We found that MST4 expression in human liver biopsies was positively correlated with the key features of NAFLD (i.e., hepatic steatosis, lobular inflammation, and hepatocellular ballooning). Furthermore, the silencing of MST4 attenuated lipid accumulation in human hepatocytes by stimulating β‐oxidation and triacylglycerol secretion, while inhibiting fatty acid influx and lipid synthesis. Conversely, overexpression of MST4 in human hepatocytes exacerbated fat deposition by suppressing mitochondrial fatty acid oxidation and triacylglycerol efflux, while enhancing lipogenesis. In parallel to these reciprocal alterations in lipid storage, we detected substantially decreased or aggravated oxidative/endoplasmic reticulum stress in human hepatocytes with reduced or increased MST4 levels, respectively. Interestingly, MST4 protein was predominantly associated with intracellular lipid droplets in both human and rodent hepatocytes. Conclusion: Together, our results suggest that hepatic lipid droplet–decorating protein MST4 is a critical regulatory node governing susceptibility to NAFLD and warrant future investigations to address the therapeutic potential of MST4 antagonism as a strategy to prevent or mitigate the development and aggravation of this disease.